The Effects of Oil Revenue Allocation between Accumulation and Current Use on Macroeconomic Responses to External and Internal Shocks in a Small Oil-exporting Economy - Mukhamediyev, Bulat; Khitakhunov, Azimzhan; Temerbulatova, Zhansaya; Mukhamediyeva, Aliya; Sabikenova, Aidana (International Journal of Energy Economics and Policy, 2026)
All economies face risks of potential shocks, including oil-exporting countries. However, they can influence their impacts by changing the distribution of oil export revenues. However, the impact of different strategies for using rent income on the stability of macroeconomic indicators in the face of external and domestic shocks has been little studied. This study, using a dynamic general equilibrium (DSGE) model, examines the impact of the distribution of oil revenues between accumulation and current expenditure on the macroeconomic responses of a small oil-exporting economy to external and domestic shocks. Within this model, the study identified how different distributions of oil revenues affect the responses of economic indicators such as GDP, consumption, inflation, interest rates, real effective exchange rates, and net exports. The effects of shocks to the global oil price, total factor productivity, labor preferences, external demand for oil, and output in the rest of the world were considered. Although even small changes in the distribution of oil revenues can influence the responses of macroeconomic indicators to shocks, conclusions about the significance of differences between responses were drawn based on their estimated 90% confidence intervals. The results of this study can be considered by policymakers in oil-exporting countries.